2000
DOI: 10.1016/s0896-6273(00)00083-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Midbrain Dopaminergic Neurons from ES Cells by Stromal Cell–Derived Inducing Activity

Abstract: We have identified a stromal cell-derived inducing activity (SDIA) that promotes neural differentiation of mouse ES cells. SDIA accumulates on the surface of PA6 stromal cells and induces efficient neuronal differentiation of cocultured ES cells in serum-free conditions without use of either retinoic acid or embryoid bodies. BMP4, which acts as an antineuralizing morphogen in Xenopus, suppresses SDIA-induced neuralization and promotes epidermal differentiation. A high proportion of tyrosine hydroxylase-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
1,068
2
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,196 publications
(1,123 citation statements)
references
References 40 publications
40
1,068
2
13
Order By: Relevance
“…27 The group of H Kawasaki has demonstrated that BMP-4 is able to redirect neuroectodermal precursors towards epidermal commitment. 6 However, the mechanism of BMP-4 neural inhibition remained unexplored so far. Here, we demonstrate that BMP-4, through the Smad signaling pathway, induces the apoptotic cell death of neuroectodermal precursor cells already engaged in the neural cell fate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…27 The group of H Kawasaki has demonstrated that BMP-4 is able to redirect neuroectodermal precursors towards epidermal commitment. 6 However, the mechanism of BMP-4 neural inhibition remained unexplored so far. Here, we demonstrate that BMP-4, through the Smad signaling pathway, induces the apoptotic cell death of neuroectodermal precursor cells already engaged in the neural cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of glial (Sox10, GFAP) markers confirmed the requirement of appropriate culture conditions to induce astrocytic (GFAP) and oligodendrocytic (Sox10) differentiation within this in vitro culture model. 6,19 Furthermore, no differentiation toward endodermal (AFP) and mesodermal (brachyury) lineages was observed ( Figure 1B).…”
Section: Bmp-4 Inhibits the Differentiation Of Mouse Es Cells Into Nementioning
confidence: 99%
See 3 more Smart Citations